2001
DOI: 10.1046/j.1365-263x.2001.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

A study on the measurement of occlusal force and masticatory efficiency in school age Japanese children

Abstract: It is obvious from the results that the occlusal force of Japanese school age children is decreasing. A t-test of both masticatory efficiency and occlusal force showed no significant sex differences for children at 7 and 8 years old. However, 9 year-old boys showed significantly higher values compared with 9 year-old girls in both measurements. No significant difference was seen between 7 and 8 year-old children in both measurements. However, 9 year-old children showed significantly higher values when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 4 publications
5
25
1
Order By: Relevance
“…Comparisons with other studies are tricky, since values of masticatory performance may be confounded by the use of different methodologies. Nevertheless, the results of bite force were similar to those of other studies in pre-school children, 14,15 despite the different devices used.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Comparisons with other studies are tricky, since values of masticatory performance may be confounded by the use of different methodologies. Nevertheless, the results of bite force were similar to those of other studies in pre-school children, 14,15 despite the different devices used.…”
Section: Discussionsupporting
confidence: 87%
“…The increasing softness of food is an environmental factor that might exert a strong influence on occlusal force. 15 The occlusal force of children who mainly ate a soft diet was significantly lower than that of those who ate a more fibrous diet.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Maki, Nishioka, Morimoto, Naito, and Kimura (2001) reported that a change in diet habit can result in a decrease in bite force in school‐age children. Therefore, masticatory exercise seems important in improving masticatory disturbance and deficiency.…”
Section: Introductionmentioning
confidence: 99%